Rubber composition for tires and pneumatic tire

By using silica and aluminate of a specific surface area in the tire rubber composition, combined with modified SBR, the contradiction between slippery performance and steering stability is solved, and the tire is excellent initial grip on slippery road surfaces and stable steering during long driving is achieved.

JP7626307B2Active Publication Date: 2025-02-07SUMITOMO RUBBER INDUSTRIES LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021042606
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-16
Publication Date
2025-02-07
Estimated Expiration
2036-04-06

AI Technical Summary

Technical Problem

While improving slippery performance, it is difficult to maintain good steering stability, especially during long driving. In the prior art, aluminate is used in the prior art and can easily lead to a rise in the tire temperature, affecting steering stability.

Method used

Silica and aluminate with specific surface areas of CTAB and BET are used in combination with modified styrene-butadiene rubber (SBR) of specific particle size and structure to improve the slippery performance and steering stability of the tire rubber composition.

Benefits of technology

The tires are achieved excellent initial grip performance on slippery roads and stable steering performance during long driving, while also suppressing the heat increase caused by aluminate and improving the overall performance of the tire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626307000004
    Figure 0007626307000004
  • Figure 0007626307000001
    Figure 0007626307000001
  • Figure 0007626307000002
    Figure 0007626307000002
Patent Text Reader

Abstract

To provide a tire rubber composition which can achieve both of (initial) wet skid performance and steering stability (particularly, steering stability in long-time driving), and a pneumatic tire prepared therewith.SOLUTION: This invention relates to a tire rubber composition that contains aluminum hydroxide and silica, the silica having a CTAB specific surface of 180 m2 / g or more and a BET specific surface of 185 m2 / g or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a rubber composition for tires and a pneumatic tire using the same. [Background technology]

[0002] In recent years, the performance requirements for tires have been increasing, and improvements in the wear resistance of the tread and wet skid performance are being required. As a method for satisfying these performance requirements, Patent Document 1 discloses a rubber composition for tires that can improve wet skid performance by compounding silica, but the steering stability has not been studied in detail, and there is still room for improvement.

[0003] In addition, attempts have been made to improve wet skid performance by utilizing the property that when aluminum hydroxide is blended into a rubber composition, the rubber composition becomes soft at low temperature and low strain. However, there is a problem that the tire temperature rises when driven for a long time, and the handling stability deteriorates. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2008-31244 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention aims to solve the above problems and provide a rubber composition for tires that can achieve both wet skid performance (initial stage) and steering stability (particularly steering stability during long-term driving), and a pneumatic tire using the same. [Means for solving the problem]

[0006] The present inventors have found that by combining silica having a CTAB specific surface area and a BET specific surface area not less than specific values ​​with aluminum hydroxide, it is possible to achieve both wet skid performance (initial stage) and handling stability (particularly handling stability during long-term driving), and have completed the present invention.

[0007] The present invention includes aluminum hydroxide and silica, the silica having a CTAB specific surface area of ​​180 m 2 / g or more, BET specific surface area is 185m 2 / g or more.

[0008] The silica preferably has an aggregate size of 30 nm or more.

[0009] The aluminum hydroxide preferably has an average particle size of 10 μm or less.

[0010] The rubber composition is preferably used in a tread. The present invention also relates to a pneumatic tire using the above rubber composition. The pneumatic tire is preferably a racing tire. Effect of the Invention

[0011] According to the present invention, a rubber composition for tires contains aluminum hydroxide and silica having a CTAB specific surface area and BET specific surface area of ​​at least specific values, so that a pneumatic tire can be provided that can achieve both wet skid performance (initial stage) and driving stability (particularly driving stability during long-term driving). This is because, even when aluminum hydroxide is blended, by blending silica having a CTAB specific surface area and BET specific surface area of ​​at least specific values, the complex modulus at 40°C (E * It is presumed that this is because the elastic modulus (Ag) and loss tangent (tan δ) are improved, and the stability of the rubber composition is improved. [Brief description of the drawings]

[0012] [Figure 1]FIG. 2 is a diagram showing a pore distribution curve. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The rubber composition for a tire of the present invention contains aluminum hydroxide and silica having a CTAB specific surface area and a BET specific surface area not less than specific values.

[0014] Examples of the rubber component include diene rubbers such as natural rubber (NR), isoprene rubber (IR), butadiene rubber (BR), styrene butadiene rubber (SBR), epoxidized natural rubber (ENR), acrylonitrile butadiene rubber (NBR), chloroprene rubber (CR), butyl rubber (IIR), and styrene-isoprene-butadiene copolymer rubber (SIBR). These diene rubbers may be used alone or in combination of two or more. Among them, SBR is preferred because of its excellent rigidity (high glass transition temperature).

[0015] Examples of SBR include emulsion-polymerized styrene-butadiene rubber (E-SBR) and solution-polymerized styrene-butadiene rubber (S-SBR).

[0016] The bound styrene content of SBR is preferably 50% by mass or less, more preferably 40% by mass or less. If it exceeds 50% by mass, it may be too hard at low temperatures, and the wet skid performance (wet grip performance) may deteriorate. In addition, the bound styrene content of SBR is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 20% by mass or more. If it is less than 5% by mass, sufficient rigidity may not be obtained, and sufficient steering stability may not be obtained. The amount of bound styrene is H 1 - Calculated by NMR measurement.

[0017] In addition, modified SBR can be preferably used because it can improve breaking strength, thereby suppressing the deterioration of abrasion resistance caused by the incorporation of aluminum hydroxide.

[0018] Modified SBR includes emulsion polymerization modified SBR (modified E-SBR) and solution polymerization modified SBR (modified S-SBR). Generally, it is easier to control the molecular weight with solution polymerization. On the other hand, with emulsion polymerization, it is difficult to control the molecular weight, and tan δ tends to be high.

[0019] The amount of bound styrene in the modified SBR is preferably 50% by mass or less, more preferably 40% by mass or less. If it exceeds 50% by mass, it may be too hard at low temperatures, and the wet skid performance (wet grip performance) may deteriorate. In addition, the amount of bound styrene in the modified SBR is preferably 5% by mass or more, more preferably 10% by mass or more. If it is less than 5% by mass, sufficient rigidity may not be obtained, and sufficient steering stability may not be obtained. The amount of bound styrene is H 1 - Calculated by NMR measurement.

[0020] The modified SBR preferably used is one that is coupled with tin, silicon, etc. The coupling method for modified SBR is, for example, a method in which an alkali metal (such as Li) or an alkaline earth metal (such as Mg) at the molecular chain end of the modified SBR is reacted with a tin halide or a silicon halide according to a conventional method.

[0021] The modified SBR is a copolymer of styrene and butadiene, and preferably has a primary amino group or an alkoxysilyl group. The primary amino group may be bonded to any of the polymerization initiation end, polymerization termination end, polymer main chain, and side chain, but is preferably introduced to the polymerization initiation end or polymerization termination end from the viewpoint of suppressing energy loss from the polymer end and improving hysteresis loss characteristics.

[0022] Among the modified SBRs produced by solution polymerization, those in which styrene-butadiene rubber (SBR) is modified with a compound represented by the following formula (1) (modified S-SBR) are particularly preferred. This makes it easier to control the molecular weight of the polymer, reduces low molecular weight components that increase tan δ, and further strengthens the bond between silica and the polymer chain, improving abrasion resistance and providing sufficient rigidity.

[0023] [ka] (In the formula, R 1 , R 2 and R 3 R may be the same or different and represents an alkyl group, an alkoxy group, a silyloxy group, an acetal group, a carboxyl group, a mercapto group, or a derivative thereof. 4 and R 5 are the same or different and represent a hydrogen atom or an alkyl group; and n represents an integer.

[0024] In the compound represented by the above formula (1), R 1 , R 2 and R 3 are the same or different and represent an alkyl group, an alkoxy group, a silyloxy group, an acetal group, a carboxyl group (-COOH), a mercapto group (-SH), or a derivative thereof. Examples of the alkyl group include alkyl groups having 1 to 4 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, and a t-butyl group. Examples of the alkoxy group include alkoxy groups having 1 to 8 carbon atoms (preferably having 1 to 6 carbon atoms, more preferably having 1 to 4 carbon atoms), such as a methoxy group, an ethoxy group, an n-propoxy group, an isopropoxy group, an n-butoxy group, and a t-butoxy group. The alkoxy group also includes cycloalkoxy groups (cycloalkoxy groups having 5 to 8 carbon atoms, such as a cyclohexyloxy group), and aryloxy groups (aryloxy groups having 6 to 8 carbon atoms, such as a phenoxy group, a benzyloxy group, and the like).

[0025] Examples of the silyloxy group include silyloxy groups substituted with an aliphatic group or an aromatic group having 1 to 20 carbon atoms (such as a trimethylsilyloxy group, a triethylsilyloxy group, a triisopropylsilyloxy group, a diethylisopropylsilyloxy group, a t-butyldimethylsilyloxy group, a t-butyldiphenylsilyloxy group, a tribenzylsilyloxy group, a triphenylsilyloxy group, and a tri-p-xylylsilyloxy group).

[0026] Examples of the acetal group include groups represented by -C(RR')-OR" and -OC(RR')-OR". Examples of the former include a methoxymethyl group, an ethoxymethyl group, a propoxymethyl group, a butoxymethyl group, an isopropoxymethyl group, a t-butoxymethyl group, and a neopentyloxymethyl group, and examples of the latter include a methoxymethoxy group, an ethoxymethoxy group, a propoxymethoxy group, an i-propoxymethoxy group, an n-butoxymethoxy group, a t-butoxymethoxy group, an n-pentyloxymethoxy group, an n-hexyloxymethoxy group, a cyclopentyloxymethoxy group, and a cyclohexyloxymethoxy group. R 1 , R 2 and R 3 As the alkyl group, an alkoxy group is preferable, because this makes it possible to obtain excellent low heat build-up properties, fracture strength, crack growth resistance, and rigidity.

[0027] R 4 and R 5 Examples of the alkyl group include the same groups as those mentioned above.

[0028] The integer n is preferably 1 to 5. This allows for excellent low heat build-up properties, fracture strength, crack growth resistance, and rigidity to be obtained. Furthermore, n is more preferably 2 to 4, and most preferably 3. When n is 0, it is difficult for silicon atoms and nitrogen atoms to bond, and when n is 6 or more, the effect as a modifier is reduced.

[0029] Specific examples of the compound represented by the above formula (1) include 3-aminopropyldimethylmethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylethyldimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyldimethylethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyldimethylbutoxysilane, 3-aminopropylmethyldibutoxysilane, dimethylaminomethyltrimethoxysilane, 2-dimethylaminoethyltrimethoxysilane, 3-dimethylaminopropyltrimethoxysilane, 4-dimethylaminobutyltrimethoxysilane, dimethylaminomethyldimethoxymethylsilane, 2-dimethylaminoethyldimethoxymethylsilane, 3-dimethylaminopropyldimethoxymethylsilane, 4-dimethylaminobutyldimethoxymethylsilane, dimethylaminomethyltriethoxysilane, 2-dimethylaminoethyltriethoxysilane, 3-dimethylaminopropyltriethoxysilane, 4-dimethylaminobutyltriethoxysilane, xysilane, dimethylaminomethyldiethoxymethylsilane, 2-dimethylaminoethyldiethoxymethylsilane, 3-dimethylaminopropyldiethoxymethylsilane, 4-dimethylaminobutyldiethoxymethylsilane, diethylaminomethyltrimethoxysilane, 2-diethylaminoethyltrimethoxysilane, 3-diethylaminopropyltrimethoxysilane, 4-diethylaminobutyltrimethoxysilane, diethylaminomethyldimethoxymethylsilane, 2-diethylaminoethyldimethoxymethylsilane, 3- Examples of such silanes include diethylaminopropyl dimethoxymethylsilane, 4-diethylaminobutyl dimethoxymethylsilane, diethylaminomethyl triethoxysilane, 2-diethylaminoethyl triethoxysilane, 3-diethylaminopropyl triethoxysilane, 4-diethylaminobutyl triethoxysilane, diethylaminomethyl diethoxymethylsilane, 2-diethylaminoethyl diethoxymethylsilane, 3-diethylaminopropyl diethoxymethylsilane, 4-diethylaminobutyl diethoxymethylsilane, etc. These may be used alone or in combination of two or more.

[0030] The method of modifying styrene-butadiene rubber with the compound (modifier) ​​represented by the above formula (1) can be a conventionally known method such as the methods described in JP-B-6-53768, JP-B-6-57767, etc. For example, it is sufficient to contact the styrene-butadiene rubber with the modifier, and examples of the method include a method of polymerizing the styrene-butadiene rubber and adding a predetermined amount of the modifier to the polymer rubber solution, and a method of adding the modifier to the styrene-butadiene rubber solution and reacting it.

[0031] The total content of SBR and modified SBR in 100% by mass of the rubber component is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 100% by mass. If it is less than 80% by mass, sufficient abrasion resistance and high rigidity may not be obtained.

[0032] The content of modified SBR in the total content of SBR and modified SBR (100% by mass) is preferably 40% by mass or more, more preferably 50% by mass or more. When it is 40% by mass or more, abrasion resistance and high rigidity can be obtained more effectively. There is no particular upper limit to the content.

[0033] In the present invention, the CTAB specific surface area is 180 m 2 / g or more, BET specific surface area is 185m 2 / g or more of silica (hereinafter also referred to as "fine particle silica"). By blending such fine particle silica, even when aluminum hydroxide is blended, it is possible to achieve both wet skid performance (initial stage) and driving stability (particularly, driving stability during long-term driving).

[0034] The CTAB (cetyltrimethylammonium bromide) specific surface area of ​​the fine silica particles is preferably 190 m 2 / g or more, more preferably 195m 2 / g or more, more preferably 197m 2 / g or more. CTAB specific surface area is 180m 2 If it is less than 1.0 μm / g, there is a risk that sufficient wet skid performance (wet grip performance) cannot be obtained. The CTAB specific surface area is preferably 500 m 2 / g or less, more preferably 300m 2 / g or less, more preferably 250m 2 / g or less. CTAB specific surface area is 500m 2 If it exceeds 1 / g, dispersibility may deteriorate and sufficient abrasion resistance may not be obtained. The CTAB specific surface area is measured in accordance with ASTM D3765-92.

[0035] The BET specific surface area of ​​the fine silica particles is preferably 190 m 2 / g or more, more preferably 195m 2 / g or more, more preferably 210m 2 / g or more. BET specific surface area is 185m 2 If it is less than 1 / g, sufficient abrasion resistance may not be obtained. The BET specific surface area is preferably 500 m 2 / g or less, more preferably 300m 2 / g or less, more preferably 260m 2 / g or less. BET specific surface area is 500m 2 If it exceeds 1 / g, the tire becomes hard and there is a risk that sufficient wet skid performance (wet grip performance) cannot be obtained. The BET specific surface area of ​​silica is measured in accordance with ASTM D3037-81.

[0036] The aggregate size of the fine particle silica is 30nm or more, preferably 35nm or more, more preferably 40nm or more, even more preferably 45nm or more, particularly preferably 50nm or more, and most preferably 55nm or more.The aggregate size is preferably 100nm or less, more preferably 80nm or less, even more preferably 70nm or less, and particularly preferably 65nm or less.By having such an aggregate size, it is possible to provide excellent reinforcement, wet skid performance (initial stage), and steering stability (particularly steering stability when driving for a long time) while having good dispersibility.

[0037] The aggregate size is also called the aggregate diameter or the maximum frequency Stokes equivalent diameter, and corresponds to the particle diameter when a silica aggregate consisting of a plurality of primary particles is regarded as one particle. The aggregate size can be measured, for example, using a disk centrifugal sedimentation type particle size distribution analyzer such as BI-XDC (manufactured by Brookhaven Instruments Corporation).

[0038] Specifically, it can be measured using BI-XDC by the following method. 3.2 g of silica and 40 mL of deionized water are added to a 50 mL tall beaker and the beaker containing the silica suspension is placed in an ice-filled crystallizer. The beaker is prepared by disintegrating the suspension for 8 minutes using an ultrasonic probe (1500 watt 1.9 cm VIBRACELL ultrasonic probe (Bioblock, used at 60% of maximum power)). 15 mL of the sample is introduced into the disk, stirred and measured under the conditions of stationary mode, analysis time 120 minutes, and density 2.1. On the recorder of the instrument, the values ​​of the 16%, 50% (or median) and 84% mass passing diameters and the mode value are recorded. (The derivative of the cumulative particle size curve gives the distribution curve its maximum abscissa, called the mode.)

[0039] Using this disk centrifuge particle size analysis method, silica was dispersed in water by ultrasonic disintegration, and then D w After analysis (sedimentation for 120 minutes), the particle size distribution is calculated by a particle size analyzer. w The weight average particle size, expressed as: is calculated by the following formula:

number

[0040] The average primary particle diameter of the fine silica particles is preferably 25 nm or less, more preferably 22 nm or less, even more preferably 17 nm or less, and particularly preferably 14 nm or less. The lower limit of the average primary particle diameter is not particularly limited, but is preferably 3 nm or more, more preferably 5 nm or more, and even more preferably 7 nm or more. Although it has such a small average primary particle diameter, the dispersibility of silica can be further improved by the carbon black-like structure having the above aggregate size, and the reinforcement, abrasion resistance, wet skid performance (initial stage), and steering stability (particularly, steering stability when driving for a long time) can be further improved. The average primary particle size of the finely divided silica can be determined by observing with a transmission or scanning electron microscope, measuring 400 or more primary silica particles observed within a visual field, and averaging the measurements.

[0041] The D50 of the fine silica particles is preferably 7.0 μm or less, more preferably 5.5 μm or less, and even more preferably 4.5 μm or less. If it exceeds 7.0 μm, there is a risk that sufficient rigidity cannot be obtained. The D50 of the fine silica particles is preferably 2.0 μm or more, more preferably 2.5 μm or more, and even more preferably 3.0 μm or more. If it is less than 2.0 μm, it is hard and there is a risk that sufficient wet skid performance (wet grip performance) cannot be obtained. Here, D50 is the median diameter of the particulate silica that is smaller than the median diameter of 50% by weight of the particles.

[0042] Furthermore, the proportion of particulate silica having a particle size of more than 18 μm is preferably 6% by mass or less, more preferably 4% by mass or less, and even more preferably 1.5% by mass or less, which provides good dispersibility of silica and desired performance. The D50 of the fine particle silica, and the proportion of silica having a given particle size, are measured by the following method.

[0043] The aggregation of the aggregates is assessed by carrying out particle size measurements (using laser diffraction) on suspensions of previously ultrasonically disintegrated silica. This method measures the disintegrability of the silica (disintegration of silica from 0.1 to several tens of microns). The ultrasonic disintegration is carried out using a Bioblock VIBRACELL sound generator (600 W) equipped with a 19 mm diameter probe (operated at 80% of maximum power). The particle size measurements are carried out by laser diffraction on a Malvern Mastersizer 2000 particle size analyzer.

[0044] Specifically, it is measured by the following method. 1 gram of silica is weighed into a pillbox (height 6 cm and diameter 4 cm) and deionized water is added to make the mass 50 grams to prepare an aqueous suspension containing 2% silica, which is homogenized by magnetic stirring for 2 minutes. Then ultrasonic disintegration is carried out for 420 seconds, and after the entire homogenized suspension is introduced into the container of the particle size analyzer, a particle size measurement is carried out.

[0045] The pore volume distribution width W of the fine particle silica is preferably 1.0 or more, more preferably 1.5 or more, even more preferably 2.0 or more, and particularly preferably 2.5 or more. The pore distribution width W is preferably 5.0 or less, more preferably 4.5 or less, even more preferably 4.0 or less, and particularly preferably 3.5 or less. Such a broad pore distribution can improve the dispersibility of silica and obtain the desired performance. The pore distribution width W of the pore volume of silica can be measured by the following method.

[0046] The pore volume of particulate silica is measured by mercury porosimetry. A sample of silica is pre-dried in an oven at 200°C for 2 hours, then placed in a test vessel and evacuated within 5 minutes after removal from the oven. The pore diameter (AUTOPORE III 9420 Powder Technology Porosimeter) is calculated by the Washburn equation at a contact angle of 140° and a surface tension γ of 484 dynes / cm (or N / m).

[0047] The pore distribution width W can be determined from a pore distribution curve as shown in Figure 1, which is a function of pore diameter (nm) and pore volume (mL / g). That is, the value of diameter Xs (nm) that gives the peak value Ys (mL / g) of the pore volume is recorded, and then a line of Y = Ys / 2 is plotted, and points a and b where this line intersects with the pore distribution curve are determined. When the horizontal coordinates (nm) of points a and b are Xa and Xb, respectively (Xa>Xb), the pore distribution width W corresponds to (Xa-Xb) / Xs.

[0048] The diameter Xs (nm) giving the peak value Ys of the pore volume in the pore distribution curve of the fine particle silica is preferably 10 nm or more, more preferably 15 nm or more, even more preferably 18 nm or more, particularly preferably 20 nm or more, and is preferably 60 nm or less, more preferably 35 nm or less, even more preferably 28 nm or less, particularly preferably 25 nm or less. If it is within the above range, fine particle silica excellent in dispersibility and reinforcing properties can be obtained.

[0049] The amount of the fine silica particles is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, even more preferably 15 parts by mass or more, particularly preferably 20 parts by mass or more, and most preferably 30 parts by mass or more, based on 100 parts by mass of the rubber component. If it is less than 5 parts by mass, sufficient rigidity may not be obtained. The amount of the fine silica particles is preferably 150 parts by mass or less, more preferably 100 parts by mass or less, and even more preferably 80 parts by mass or less. If it exceeds 150 parts by mass, dispersibility may deteriorate and sufficient wear resistance may not be obtained.

[0050] The rubber composition of the present invention may contain silica other than the above-mentioned fine particle silica. In this case, the total content of silica is preferably 30 parts by mass or more, more preferably 40 parts by mass or more, and even more preferably 45 parts by mass or more, based on 100 parts by mass of the rubber component. The total content is preferably 200 parts by mass or less, more preferably 150 parts by mass or less, and even more preferably 100 parts by mass or less. When the content is less than the lower limit or exceeds the upper limit, the same tendency as the above-mentioned fine particle silica content is observed.

[0051] In the rubber composition of the present invention, it is preferable to further compound a silane coupling agent. By compounding the silane coupling agent, the abrasion resistance can be improved. As the silane coupling agent, a conventionally known silane coupling agent can be used, for example, bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(4-triethoxysilylbutyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(4-trimethoxysilylbutyl)tetrasulfide, bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(4-trimethoxysilylbutyl)tetrasulfide, bis(3-triethoxysilylpropyl)tetrasulfide, ) trisulfide, bis(2-triethoxysilylethyl) trisulfide, bis(4-triethoxysilylbutyl) trisulfide, bis(3-trimethoxysilylpropyl) trisulfide, bis(2-trimethoxysilylethyl) trisulfide, bis(4-trimethoxysilylbutyl) trisulfide, bis(3-triethoxysilylpropyl) disulfide, bis(2-triethoxysilylethyl) disulfide, bis(4-trimethoxysilylbutyl) disulfide, bis(3-trimethoxy silylpropyl) disulfide, bis(2-trimethoxysilylethyl) disulfide, bis(4-trimethoxysilylbutyl) disulfide, 3-trimethoxysilylpropyl-N,N-dimethylthiocarbamoyl tetrasulfide, 3-triethoxysilylpropyl-N,N-dimethylthiocarbamoyl tetrasulfide, 2-triethoxysilylethyl-N,N-dimethylthiocarbamoyl tetrasulfide, 2-trimethoxysilylethyl-N,N-dimethylthiocarbamoyl tetrasulfide, Sulfide-based compounds such as 3-trimethoxysilylpropyl benzothiazolyl tetrasulfide, 3-triethoxysilylpropyl benzothiazole tetrasulfide, and 3-trimethoxysilylpropyl methacrylate monosulfide; mercapto-based compounds such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 2-mercaptoethyltrimethoxysilane, and 2-mercaptoethyltriethoxysilane; vinyl-based compounds such as vinyltriethoxysilane and vinyltrimethoxysilane;Examples of the silanes include amino-based silanes such as 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltriethoxysilane, and 3-(2-aminoethyl)aminopropyltrimethoxysilane; glycidoxy-based silanes such as γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, and γ-glycidoxypropylmethyldimethoxysilane; nitro-based silanes such as 3-nitropropyltrimethoxysilane and 3-nitropropyltriethoxysilane; chloro-based silanes such as 3-chloropropyltrimethoxysilane, 3-chloropropyltriethoxysilane, 2-chloroethyltrimethoxysilane, and 2-chloroethyltriethoxysilane; and the like. Among these, bis(3-triethoxysilylpropyl)tetrasulfide and bis(3-triethoxysilylpropyl)disulfide are preferred because of their good processability. These silane coupling agents may be used alone or in combination of two or more kinds.

[0052] The content of the silane coupling agent is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, even more preferably 2 parts by mass or more, particularly preferably 5 parts by mass or more, and most preferably 10 parts by mass or more, based on 100 parts by mass of silica. If it is less than 0.5 parts by mass, sufficient abrasion resistance may not be obtained. The content is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, and even more preferably 20 parts by mass or less. If it exceeds 30 parts by mass, dispersibility may deteriorate.

[0053] In the present invention, aluminum hydroxide is used. In the present invention, aluminum hydroxide includes alumina hydrate.

[0054] The average particle size of the aluminum hydroxide is preferably 10 μm or less, more preferably 5 μm or less, and even more preferably 3 μm or less. If it exceeds 10 μm, the wet skid performance (initial stage) and the steering stability (particularly the steering stability during long-term driving) may not be sufficiently obtained. The average particle size of the aluminum hydroxide is preferably 0.05 μm or more, more preferably 0.1 μm or more. If it is less than 0.05 μm, the dispersibility may be deteriorated and sufficient abrasion resistance may not be obtained.

[0055] In the present invention, the average particle size of aluminum hydroxide was measured using a transmission or scanning electron microscope. The average particle size means the major axis, which is the longest length when the aluminum hydroxide powder is projected onto a projection plane while changing the direction of the aluminum hydroxide powder relative to the projection plane.

[0056] The content of aluminum hydroxide is preferably 1 part by mass or more, more preferably 2 parts by mass or more, even more preferably 10 parts by mass or more, and particularly preferably 20 parts by mass or more, based on 100 parts by mass of the rubber component. If it is less than 1 part by mass, sufficient wet skid performance (wet grip performance) may not be obtained. The content of aluminum hydroxide is preferably 60 parts by mass or less, more preferably 50 parts by mass or less. If it exceeds 60 parts by mass, dispersibility may deteriorate, and sufficient abrasion resistance may not be obtained.

[0057] In addition to the above-mentioned components, the rubber composition of the present invention may appropriately contain compounding agents generally used in the production of rubber compositions, for example, reinforcing fillers such as carbon black and clay, zinc oxide, stearic acid, various antioxidants, vulcanizing agents such as oil, wax, sulfur and sulfur-containing compounds, and vulcanization accelerators.

[0058] The rubber composition of the present invention preferably contains carbon black. Examples of carbon black that can be used include, but are not limited to, GPF, FEF, HAF, ISAF, SAF, etc. By blending carbon black, it is possible to increase the reinforcing property and improve the abrasion resistance.

[0059] The nitrogen adsorption specific surface area (N2SA) of carbon black is 90m 2 / g or more is preferable, and 100m 2 / g or more is more preferable. 2 If the specific surface area is less than 200 m / g, sufficient rigidity may not be obtained. 2 / g or less is preferable, and 190m 2 / g or less is more preferable. 2 If it exceeds 1 / g, the wet skid performance (initial stage) may be deteriorated. The nitrogen adsorption specific surface area of ​​carbon black is determined by Method A of JIS K6217.

[0060] When the rubber composition contains carbon black, the carbon black content is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more, based on 100 parts by mass of the rubber component. If the carbon black content is less than 5 parts by mass, sufficient abrasion resistance and rigidity may not be obtained. The carbon black content is preferably 100 parts by mass or less, more preferably 90 parts by mass or less, even more preferably 70 parts by mass or less, particularly preferably 50 parts by mass or less, and most preferably 30 parts by mass or less. If the carbon black content exceeds 100 parts by mass, wet skid performance (initial stage) may be reduced.

[0061] In the present invention, as the antiaging agent, for example, amine-based antiaging agents, quinoline-based antiaging agents, monophenol-based antiaging agents, etc. can be used. These antiaging agents may be used alone or in combination of two or more. Among them, amine-based antiaging agents and quinoline-based antiaging agents can be preferably used, and it is more preferable to use amine-based antiaging agents and quinoline-based antiaging agents in combination, because they can effectively exhibit heat resistance and fatigue resistance, and can effectively suppress the deterioration of steering stability during long-term driving.

[0062] Examples of the amine-based antiaging agent include amine derivatives such as diphenylamine and p-phenylenediamine. Examples of the diphenylamine derivatives include p-(p-toluenesulfonylamide)-diphenylamine and octylated diphenylamine. Examples of the p-phenylenediamine derivatives include N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (6PPD), N-phenyl-N'-isopropyl-p-phenylenediamine (IPPD), and N,N'-di-2-naphthyl-p-phenylenediamine.

[0063] Examples of quinoline-based antioxidants include 2,2,4-trimethyl-1,2-dihydroquinoline polymers and 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline.

[0064] Examples of monophenol-based antiaging agents include 2,6-di-tert-butyl-4-methylphenol, 2,6-di-tert-butyl-4-ethylphenol, 2,6-di-tert-butylphenol, 1-oxy-3-methyl-4-isopropylbenzene, butylhydroxyanisole, 2,4-dimethyl-6-tert-butylphenol, n-octadecyl-3-(4'-hydroxy-3',5'-di-tert-butylphenyl)propionate, and styrenated phenol.

[0065] The content of the antioxidant is preferably 1 part by mass or more, more preferably 2 parts by mass or more, based on 100 parts by mass of the rubber component. If it is less than 1 part by mass, the breaking properties may not be improved, and the deterioration of the steering stability during long-term driving may not be effectively suppressed. The content is preferably 15 parts by mass or less, more preferably 10 parts by mass or less. If it exceeds 15 parts by mass, blooming may occur on the surface.

[0066] When the rubber composition uses an amine-based antioxidant and a quinoline-based antioxidant in combination, the compounding ratio of the amine-based antioxidant to the quinoline-based antioxidant (amine-based antioxidant (parts by mass) / quinoline-based antioxidant (parts by mass)) is preferably at least 1, more preferably at least 1.2. If the ratio is less than 1, sufficient fatigue resistance cannot be obtained, and there is a risk that deterioration of steering stability during long-term driving cannot be effectively suppressed. The blending ratio is preferably not more than 5, more preferably not more than 2.5. If it exceeds 5, the heat resistance effect is not sufficiently exhibited, and there is a risk that deterioration of steering stability during long-term driving cannot be effectively suppressed.

[0067] The rubber composition of the present invention can be produced by a general method. That is, the components are kneaded with a Banbury mixer, a kneader, an open roll, etc., and then vulcanized. The rubber composition can be used for each component of a tire, and is particularly suitable for use in a tread.

[0068] The pneumatic tire of the present invention is produced by a conventional method using the above rubber composition. That is, the rubber composition containing the above-mentioned components is extruded in an unvulcanized state to match the shape of each tire component such as the tread, and molded together with other tire components in a tire building machine by a normal method to form an unvulcanized tire. The unvulcanized tire is then heated and pressurized in a vulcanizer to obtain a tire.

[0069] The pneumatic tire of the present invention is preferably used as a passenger car tire, a truck / bus tire, a motorcycle tire, a racing tire, etc., and is particularly preferably used as a racing tire. The racing tire in the present invention is a tire used for racing such as karts. The pneumatic tire obtained by the present invention has excellent grip performance (wet skid performance (particularly, initial wet skid performance)) and steering stability (particularly, steering stability when driven for a long time) on a wet road surface, and is more preferably used as a racing tire for driving on a wet road surface. EXAMPLES

[0070] The present invention will be specifically described based on examples, but the present invention is not limited to these examples.

[0071] The following are examples. , reference example The various chemicals used in the comparative examples will be described below. SBR: Asahi Kasei Corporation's Tufuden 4350 (bound styrene content: 39% by mass, contains 50 parts by mass of oil per 100 parts by mass of rubber solids) Modified SBR: HPR355 manufactured by JSR Corporation (modified S-SBR, bound styrene content: 21% by mass, coupled with alkoxysilane to introduce it into the terminal, modified with a compound represented by formula (1) (R in formula (1) 1 = methoxy group, R 2 = methoxy group, R 3 = methoxy group, R 4 = hydrogen atom, R 5 = hydrogen atom, n=3) Carbon black: Diablack A (N110) (N2SA: 142m) manufactured by Mitsubishi Chemical Corporation 2 / g) Silica 1: Nipsil VN3 (CTAB specific surface area: 170 m) manufactured by Nippon Silica Industry Co., Ltd. 2 / g, BET specific surface area: 191m 2 / g, average primary particle size: 19 nm, aggregate size: 33 nm) Silica 2: Zeosil HRS 1200MP manufactured by Rhodia (CTAB specific surface area: 195 m 2 / g, BET specific surface area: 200m 2 / g, average primary particle diameter: 15 nm, aggregate size: 40 nm, D50: 6.5 μm, percentage of particles larger than 18 μm: 5.0 mass%, pore distribution width W: 0.40, diameter Xs giving the pore volume peak value in the pore distribution curve: 18.8 nm) Silica 3: Zeosil Premium 200MP (CTAB specific surface area 200 m 2 / g, BET specific surface area: 220m 2 / g, average primary particle diameter 10: nm, aggregate size: 65 nm, D50: 4.2 μm, percentage of particles larger than 18 μm: 1.0 mass%, pore distribution width W: 1.57, diameter Xs giving the pore volume peak value in the pore distribution curve: 21.9 nm) Antioxidant 6C: Santoflex 13 (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (6PPD)) manufactured by Flexis Co., Ltd. Antioxidant 224: Nocrac 224 (2,2,4-trimethyl-1,2-dihydroquinoline polymer) manufactured by Flexis Co., Ltd. Stearic acid: Paulownia wood produced by NOF Corporation Zinc oxide: Two types of zinc oxide manufactured by Mitsui Mining & Smelting Co., Ltd. Aroma oil: Process X-260 made by Japan Energy Silane coupling agent: Degussa Si69 (bis(3-triethoxysilylpropyl)tetrasulfide) Aluminum hydroxide: Showa Denko Hijilite H-43 (average particle size: 1 μm) Sulfur: Powdered sulfur manufactured by Tsurumi Chemical Industry Co., Ltd. Vulcanization accelerator NS: Noccela NS (N-tert-butyl-2-benzothiazolyl sulfenamide) manufactured by Ouchi Shinko Chemical Industry Co., Ltd.

[0072] Example 1 2、4、 5 , Reference example 3 And Comparative Examples 1 to 4 According to the composition shown in Table 1, materials other than sulfur and vulcanization accelerator were kneaded for 3 minutes at 150°C using a BP type Banbury mixer to obtain a kneaded product. Next, sulfur and vulcanization accelerator were added to the kneaded product obtained, and the mixture was kneaded for 5 minutes at 50°C using an open roll to obtain an unvulcanized rubber composition. The resulting unvulcanized rubber composition was press-vulcanized at 170° C. for 12 minutes to obtain a vulcanized rubber sheet. The unvulcanized rubber composition thus obtained was molded into a tread shape, and was then laminated with other tire components to form a tire. The tire was then vulcanized at 170° C. for 12 minutes to produce a test cart tire (tire size: 11×7.10-5).

[0073] The vulcanized rubber sheet and test cart tire thus obtained were used to carry out the following evaluations. The test results are shown in Table 1.

[0074] (1) SWELL (crosslinking density) The obtained vulcanized rubber sheet was extracted with toluene, and the volume change rate (SWELL) before and after extraction was measured. Note that the smaller the SWELL, the more the crosslinking variation can be suppressed, which is preferable.

[0075] (2) Viscoelasticity test Using a viscoelasticity spectrometer manufactured by Iwamoto Seisakusho Co., Ltd., the viscoelasticity (complex modulus E * and the loss tangent tan δ were measured. Using a viscoelasticity spectrometer manufactured by Iwamoto Seisakusho Co., Ltd., the viscoelasticity (complex modulus E * and loss tangent tan δ) were measured. In addition, in the viscoelasticity test at 40°C, E * The larger the value, the higher the rigidity and the better the handling stability. In addition, in the viscoelasticity test at 0°C, E * The smaller the value, the better the initial grip performance (initial wet skid performance).

[0076] (3) Tensile test According to JIS K 6251 "Vulcanized rubber and thermoplastic rubber - Determination of tensile properties", a tensile test was carried out using a No. 3 dumbbell-shaped rubber test piece made of the vulcanized rubber composition, and the stress at 300% elongation (M300) was measured. The tensile strength index of Comparative Example 1 was set to 100, and the M300 of each compound was expressed as an index according to the following calculation formula. Note that a larger tensile strength index indicates better abrasion wear resistance. (Tensile strength index) = (M300 of each formulation) / (M300 of Comparative Example 1) × 100

[0077] (4) Actual vehicle evaluation A test cart tire was fitted to a test cart, which was driven around a test course (wet road surface) of 2 km per lap for 8 laps, and the initial wet skid performance of the tire of Comparative Example 1 was scored as 3 points, and the test driver performed a sensory evaluation on a 5-point scale. The initial wet skid performance indicates the wet skid performance on the 1st to 4th laps. In addition, the test driver performed a sensory evaluation of the driving stability from the 5th to 8th laps on a 5-point scale. The higher the score, the better the driving stability. In addition, the appearance of the tires after eight laps was evaluated on a scale of one to five. The higher the score, the better the wear resistance.

[0078] [Table 1]

[0079] From Table 1, examples containing aluminum hydroxide and silica having a CTAB specific surface area and a BET specific surface area of ​​a specific value or more are shown. , reference example The tire with the tread pattern was able to achieve both initial wet skid performance and steering stability during long-term driving. On the other hand, the comparative example, which did not use both, was unable to achieve a good balance between the two performances. As described above, the pneumatic tire obtained by the present invention has excellent initial wet skid performance on wet road surfaces and excellent handling stability when driven for long periods of time, and therefore can effectively suppress the decrease in time associated with laps when driving on a circuit (wet road surfaces).

Claims

1. Contains aluminum hydroxide, silica, amine-based antioxidants, and quinoline-based antioxidants. The silica has a CTAB specific surface area of ​​180 m 2 / g or more, BET specific surface area is 185 m 2 / g or more, and the aggregate size is 30 nm or more; A rubber composition for tires, in which the total content of styrene-butadiene rubber and modified styrene-butadiene rubber is 90 mass % or more based on 100 mass % of the rubber component (excluding the case where modified styrene-butadiene rubber is contained).

2. 2. The rubber composition for tires according to claim 1, wherein the average particle size of the aluminum hydroxide is 10 μm or less.

3. 3. The rubber composition for tires according to claim 1, wherein the content of aluminum hydroxide is 20 to 50 parts by mass per 100 parts by mass of the rubber component.

4. The rubber composition for tires according to any one of claims 1 to 3, which is used for a tread.

5. A pneumatic tire using the rubber composition according to any one of claims 1 to 4.

6. 6. The pneumatic tire according to claim 5, which is a racing tire.

Citation Information

Patent Citations

  • Tire tread rubber composition and pneumatic tire using the same

    JP2008031244A

  • Rubber composition for tread, and tire for racing

    JP2012116983A

  • Rubber composition and pneumatic tire

    JP2015232114A

  • JPP6862671B